Cultural adaptation in the form of a mosque roof in the South Konawe District of the Southeast Sulawesi Province - Muhammad Zakaria Umar; Muhammad Arsyad (Faculty of Social and Political Science, Universitas Airlangga, 2018)
Although it is already embodied in Islamic culture, acculturation can still be traced to elements of the supporting cultures. When the religion of Islam entered into Indonesia, the original culture was not brought with them, so the previous culture was continued by Islam. When the mosque concept is embodied as a cultural product, there are various forms and various buildings involved in the mosque. Mosques located in the Middle East are diﬀerent from mosques in Indonesia. The form of the roof overlaps with that taken from the roof of ancient mosques in Indonesia. The form of roof overlap at mosques in South Konawe District has been traced by the author. This study aims to identify and analyse what cultural elements aﬀect the shape of the roof of the mosque and the form of acculturation of the cultures at the mosques in the District of South Konawe. This research was used a qualitative descriptive method. This research concluded that the architecture as part of the Hindu cultural system, Islamic mysticism, and Europe acculturate is displayed in the roof of the mosque in the District of South Konawe. The roof shape of the two-tiered or three-storey mosque (Hindu culture and the Islamic principles of Mysticism) and the roof covered with mustaks shaped like onions (European culture) was formed by the acculturation of the three cultures.